HYBRID CONTRACTS AND SHARIAH REGULATORY TRANSFORMATION IN ISLAMIC BANKING : EVIDENCE FROM ACEH - Lia Murlisa; Muhammad Maulana; Nilam Sari (JURNAL HAKAM, 2026)
The implementation of the Qanun on Islamic Financial Institutions (Qanun LKS) in Aceh has transformed the regulatory landscape of Islamic banking by requiring all financial institutions to operate based on sharia principles. This study examines how hybrid contracts (al-‘uqud al-murakkabah) are structured and implemented within the post-Qanun regulatory framework. Unlike previous studies that mainly discuss hybrid contracts from normative and permissibility perspectives, this research analyzes their practical operation within a territorially binding sharia regulatory regime. This study employs an empirical legal approach with a socio-legal framework. The data were obtained from financing contract documents used in Islamic banking practices in Aceh, particularly murabahah bil wakalah, musyarakah mutanaqisah, and ijarah muntahiya bittamlik (IMBT), as well as relevant regulations and DSN-MUI fatwas. The data were analyzed qualitatively through content analysis, thematic coding, and document triangulation to examine contractual structures, implementation patterns, and potential sharia compliance risks. The findings indicate that hybrid contracts have become the dominant contractual structure in Islamic banking practices in Aceh following the implementation of the Qanun LKS. The integration of multiple contracts into a single financing structure functions not merely as product innovation, but as a regulatory adaptation mechanism that harmonizes regional sharia legislation, national banking regulations, and fatwa standards. However, the study also identifies several structural issues related to contract sequencing, clause interdependence, and documentation consistency that may create potential sharia non-compliance risks. This study argues that the institutionalization of sharia regulation in Aceh has directly influenced the reconstruction of contractual architecture in Islamic banking practices. Accordingly, hybrid contracts should be understood not only as contractual innovations, but also as institutional responses to regulatory transformation within contemporary Islamic finance.